2022
DOI: 10.1186/s40001-022-00774-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mineral density after bariatric surgery in patients of different ages or patients with different postoperative periods: a systematic review and meta-analysis

Abstract: To assess changes in bone mineral density (BMD) following bariatric surgery (BS) in patients with different bone sites, postoperative periods and ages. Twenty-two studies were included. Femoral neck (FN) BMD decreased after surgery (MD, − 0.05 g/cm2, CI − 0.10 to − 0.01, P = 0.03). Postoperative BMD decreased more in the FN and lumbar spine (LS) of patients older than 40 (FNBMD, − 0.07 g/cm2, CI − 0.13 to − 0.00, P = 0.04; LSBMD, − 0.03 g/cm2, CI − 0.05 to − 0.00, P = 0.02) or patients with a postoperative tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, the lack of aBMD variation at the lumbar spine and the reduction in bone turnover with time may suggest a limited effect of age. Our observational results are only generalizable to the same type of surgery-i.e., SG-as variations in aBMD between different surgical approaches, in particular RYGB, have been demonstrated [16,37]. Moreover, despite the relatively long time covered by our longitudinal study, we cannot exclude the possibility that other skeletal changes occur over a longer period, and this should be considered in future studies.…”
Section: Limitations and Strengthsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the lack of aBMD variation at the lumbar spine and the reduction in bone turnover with time may suggest a limited effect of age. Our observational results are only generalizable to the same type of surgery-i.e., SG-as variations in aBMD between different surgical approaches, in particular RYGB, have been demonstrated [16,37]. Moreover, despite the relatively long time covered by our longitudinal study, we cannot exclude the possibility that other skeletal changes occur over a longer period, and this should be considered in future studies.…”
Section: Limitations and Strengthsmentioning
confidence: 88%
“…Using a similar surgical procedure, Hofso et al [16] reported a similar aBMD loss around 5% at femoral neck and 7.8% at total hip, while at lumbar spine and whole body, minor variations occurred after 12 months. A recently published meta-analysis including 22 studies [37] noted an obvious aBMD loss at femoral neck and none at lumbar spine. This conclusion should be considered with caution, as some of the included studies reported an aBMD decrease at lumbar spine [21].…”
Section: Abmdmentioning
confidence: 99%
“…A recent meta-analysis comprising 22 studies evaluating BS patients found that the decrease in BMD was larger in the femoral neck than in the lumbar spine [ 15 ]. Additionally, a time-dependent loss of BMD was observed, with larger decreases found in longer follow-up periods.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout different life stages, BMD values vary, with rapid growth occurring during childhood and adolescence, culminating in peak BMD in early adulthood ( Deng et al, 2021 ). However, as individuals age, hormone levels, such as estrogen and testosterone, decline, leading to a subsequent reduction in BMD ( Ou et al, 2022 ). This loss of bone mass can increase the likelihood of developing conditions like periodontitis and arthritis while raising the risk of fractures ( Hartley et al, 2022 ; Yu and Wang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%